Two Missense CACNA1A Variants in a Single Family with Variable Neurobehavioral, Cerebellar, Epileptic, and Oculomotor Features - Ko, Pin-Yi; Glass, Ian A.; Crandall, Suzanne; Weiss, Avery; Dorschner, Michael O.; Kelly, John P.; Phillips, James O.; Lopez, Jonathan (Neuropediatrics, 2021)
We describe two novel missense variants in CACNA1A segregating in a family with variable severity of ataxia/oculomotor dysfunction, neurobehavioral impairments, and epilepsy. The most severe outcome occurred in a compound heterozygous proband, which could represent variable expression of the paternal allele or biallelic modulation of calcium channel function. Acetazolamide and lamotrigine were effective for seizure control.
Keywords: epilepsy; ataxia; oculomotor; neurobehavioral; CACNA1A